Toward A Solution of the Farm Problem - Houthakker, H. S. (The Review of Economics and Statistics, 1961)
(e) Net interest paid by government. The national income net interest total comprises total interest accruing to United States persons and governments less the total interest paid by United States governments to persons, governments, and businesses. The personal income interest total is obtained by adding to the national figure the excess of interest payments by governments over their interest receipts. Thus it measures total interest paid to United States persons.3 The share of the national total attributable to any one state is extremely difficult, if not impossible, to estimate by direct means, if this were desired. But allocation can be made more easily, although the method rests upon the same sort of fundamental and hazardous assumptions as in the case of allocating corporate income. Figures are availalble from the Department of Commerce of private interest received by residents of Texas and the United States. The Texas state income component of United States net interest paid by governments was obtained by applying the ratio obtained from the private interest figures to the United States net government interest total. The assumption here, of course, is that Texas residents' entitlement to a share of the national total of net government interest was the same as their entitlement to a share of the national total of private interest, as reflected in the payments actually made or imputed. The method also, as in the corporate income case, has the merit of conforming to the conceptual framework which emphasizes the wherereceived measure. TABLE 4.-GOVERNMENT AND BUSINESS TRANSFER PAYMENTS, TEXAS, I950-58 ($ million)